How students' writing motivation, teachers' personal and professional attributes, and writing instruction impact student writing achievement: a two-level hierarchical linear modeling study - Wang, Heqiao; Troia, Gary A. (Frontiers in Psychology, 2023)
Student motivation to write is a pivotal factor influencing their writing achievement. However, individual motivation to write is not independent of the learning environment. It also is crucial for teachers to develop their own efficacy, knowledge, and ability in writing and writing instruction to help them utilize effective instructional methods that stimulate students' motivation to write and further promote their writing achievement. Given these considerations, we utilized a two-level hierarchical linear model to examine the relationships among student motivation, teacher personal and professional traits, teacher writing instruction, and writing achievement at student and teacher levels. Our analysis of the dataset, which included 346 fourth and fifth graders nested within 41 classrooms, found that motivation had a positive predictive effect on writing ability at both student and teacher levels. Moreover, female students, fifth graders, and typically achieving students demonstrated higher writing achievement than their counterparts. While there were no significant effects of teacher efficacy, knowledge, ability, or professional development on student writing achievement, we observed that higher frequency of classroom management practices during writing instruction had a significant negative effect on student writing achievement. Our full model revealed that the relationship between student motivation and achievement was negatively moderated by teachers' increased use of instructional practices related to process features and using writing instruction materials, but positively moderated by increased use of varied teaching tactics. Overall, our findings emphasize the importance of contextual factors in understanding the complexity of student writing achievement and draw attention to the need for effective instructional practices to support students' writing development.